Inventory of non-timber forest products in Western Nepal and strategies for sustainable management - Dhakal, Pramila; Paudel, Dev R; Baral, Dilli Ram (International Journal of Environment, 2016)
Non-timber Forest Products (NTFPs) play an important role as traditional source for food, fiber, fodder, and medicine and offer income opportunities for poverty alleviation especially in rural households in Nepal who engage in a widespread trade of NTFPs. Adequate planning for sustainable use of NTFPs is imperative so we explored the inventory of multipurpose trees and herbs that are being used as NTFPs in Chitwan, Nepal. 70 households from Sukranagar and Mangalpur VDCs of Chitwan district were randomly selected and personal interviews were taken with them as well as focus group discussions were done. The community had been utilizing 49 plant species from the nearby community forest. Implementation of the policy of community forestry was found to have a positive impact on the sustainable production of NTFPs. More than 80% of the respondents believed that indigenous knowledge promoted sustainable NTFP production. Kurilo (Asparagus officinalis) was found to be the best NTFP for the study site. Various policy level reforms are proposed that will help in improving the sustainable production of NTFPs. Better utilization of NTFPs as well as their conservation is possible with proper trainings given to community forest users. International Journal of Environment Vol.5(3) 2016, pp.87-103